PENGARUH ADAT 7 BULANAN (PELET KANDUNG) TERHADAP PENGEMBANGAN SPIRITUALITAS IBU HAMIL DI DESA BLUMBUNGAN KEC. LARANGAN KAB. PAMEKASAN - Wusqo, Urwatul; Mujib, Mujiburrohman; Mahbub, Syukron (Program Studi Hukum Keluarga Islam UIM Pamekasan, 2024)
(One of the traditions carried out by the Madurese people, especially the Blumbungan people, is the pelet lahir or seven-month ceremony for pregnant women for their first child. They consider this ritual to be a religious event that must be carried out so that the child they are carrying can be born into the world in a perfect condition and without any shortcomings. This raises the question, why do the Madurese people really like to carry out this tradition? Is there a philosophical meaning contained in this custom? This study was conducted using field research accompanied by efforts to explore the meaning contained in this custom based on interviews and others).